2021
DOI: 10.3390/catal11111349
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Deficient WO3/TiO2/CC Nanorod Arrays for Visible-Light Photocatalytic Degradation of Methylene Blue

Abstract: At present, TiO2 is one of the most widely used photocatalytic materials. However, the narrow response range to light limits the photocatalytic performance. Herein, we reported a successful construction of self-doped R-WO3/R-TiO2/CC nanocomposites on flexible carbon cloth (CC) via electrochemical reduction to increase the oxygen vacancies (Ovs), resulting in an enhanced separation efficiency of photo-induced charge carriers. The photocurrent of R-WO3/R-TiO2/CC at −1.6 V (vs. SCE) was 2.6 times higher than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Electron charge transfer is affected by the position of the conduction band (CB) and the valence band (VB) determined for the photocatalysts Fe 3 O 4 , ZrO 2 , and TiO 2 according to Eq’s (20) and (21) ( Ojha et al, 2019 ): where in the above relations , and represent the conductivity potential, the capacitance potential and the energy band gap, is constant for all photocatalysts and represents the energy of free electrons, moreover X is the absolute electronegativity and for Fe 3 O 4 , ZrO 2 and TiO 2 the sequence has values of 5.73, 5.91 and 5.81, respectively ( Bi et al, 2020b ; Jiang et al, 2021 ; Pham et al, 2021 ). of each photocatalyst was also determined by UV-vis DRS analysis.…”
Section: Fzt Y@wds > Fz Y@s > Fe 3 Omentioning
confidence: 99%
“…Electron charge transfer is affected by the position of the conduction band (CB) and the valence band (VB) determined for the photocatalysts Fe 3 O 4 , ZrO 2 , and TiO 2 according to Eq’s (20) and (21) ( Ojha et al, 2019 ): where in the above relations , and represent the conductivity potential, the capacitance potential and the energy band gap, is constant for all photocatalysts and represents the energy of free electrons, moreover X is the absolute electronegativity and for Fe 3 O 4 , ZrO 2 and TiO 2 the sequence has values of 5.73, 5.91 and 5.81, respectively ( Bi et al, 2020b ; Jiang et al, 2021 ; Pham et al, 2021 ). of each photocatalyst was also determined by UV-vis DRS analysis.…”
Section: Fzt Y@wds > Fz Y@s > Fe 3 Omentioning
confidence: 99%
“…Theoretical calculations based on Mulliken electronegativity theory have been employed to determine the energy levels of the valence band (VB) and conduction band (CB) of both pure TiO 2 and doped TiO 2 nanomaterials [17]:…”
Section: Energy Level Structurementioning
confidence: 99%
“…Speci cally, the VB potential (E VB ), electron energy (E e = 4.5 eV), CB potential (E CB ), band gap width (E g ), and the absolute electronegativity of TiO 2 (X) were used to estimate the energies of the bands. According to previous research, the absolute electronegativity of TiO 2 has been reported to be 5.81 eV [17]. By utilizing these values, along with the formulas provided, the VB and CB energies for pure TiO 2 and doped-TiO 2 nanomaterials were computed and compiled in Table 1.…”
Section: Energy Level Structurementioning
confidence: 99%
“…Zeolite-type porous materials, combining adsorption and photocatalysis, offer a promising solution [10]. These materials, characterized by a developed surface and good thermal stability, can undergo ion exchange, allowing for changes in their chemical composition and physicochemical properties [10,11]. Titanium Silicate 10 (ETS-10) has shown promising photocatalytic applications in various fields.…”
Section: Introductionmentioning
confidence: 99%